Exploring Social Identity Transformation: A Journey through Delia Owen’s Where the Crawdads Sing - Subianto, Audrey Eveline; Winardi, Yohanes Kurniawan (J-Lalite: Journal of English Studies, 2024)
This study examines the social identity transformation of the Where the Crawdads Sing main character by using Social Identity Theory (SIT) proposed by Henri Tajfel and Turner. Tajfel and Turner divided SIT into self-categorization, social identification, and social comparison to show how these events alter the identity of Kya (the main character) transformation. This study used a qualitative approach to analyze Delia Owens' novel Where the Crawdads Sing, focusing on character development and social interactions. Secondary sources, such as literary criticisms and reviews, supplement primary data. Data analysis identifies recurring patterns and critical themes of societal identity transformation, including isolation, resilience, exclusion, and integration. This study found that Where the Crawdads Sing explores Kya's self-categorization in Barkley Cove, North Carolina. She forms a strong bond with her black friend Jumpin' and the marsh as her in-group, providing comfort and connection to the marsh. The novel contrasts Barkley Cove's out-group social identification with the marshlands, highlighting the importance of acceptance, forgiveness, and embracing one's identity in navigating complex human relationships. The social comparison explores Kya Clark's struggle for acceptance in a small town, contrasting it with the marshlands and highlighting themes of isolation and resilience.